Nanoscale coordination polymers obtained in ultrasmall liquid droplets on solid surfaces and its comparison to different synthetic volume scales. Issue 80 (12th August 2016) - Bellido, E.; González-Monje, P.; Guardingo, M.; Novio, F.; Sánchez, A.; Montero, M.; Molnar, G.; Bousseksou, A.; Ruiz-Molina, D.
Abstract : Confined synthesis and comparative study of a coordination polymer at different volume scales, from the macroscopic to the femtolitre scale. Abstract : Synthesis of coordination polymers at femtolitre scales assisted by an AFM tip has become an area of increasing interest due to the astonishing range of implications that derive from it, from gaining basic knowledge of confined reactions in femtolitre droplets to the fabrication of molecular-based devices. However, this field is still in its infancy, a reason why several new basic studies that allow us control over it are highly required. Herein we report the synthesis of [Co(CH3 COO)2 (μ-4, 4′-bpy)] in femtolitre droplets on surfaces and the results are compared with those obtained for the same reaction at different volume scales.